The importance of intestinal microbiota and its role in the nosocomial infection (Research, Society and Development, 2021)
The gastrointestinal tract houses the largest and most complex community of microorganisms, and this bacterial colonization of the human intestine by environmental microbes begins immediately after the birth. The intestinal microbiota has several important and unique functions, including metabolic functions such as the biotransformation of drugs and the digestion of dietary compounds; a mucosal barrier function by inhibiting the invasion of pathogens and an immunomodulatory function. On the other hand, some commensal bacteria can be pathogenic, causing infections if the natural host is compromised and, in predisposed hosts, the intestinal microbiota can be involved in nosocomial infection. The translocation of bacteria through the intestinal wall is considered one of the main causes of nosocomial infections. The aim of this review is to provide a comprehensive view of the human gut microbiota, its main functions, its role in health and disease, addressing the correlation between intestinal microbial composition and nosocomial infections.